1988
DOI: 10.1038/334124a0
|View full text |Cite
|
Sign up to set email alerts
|

Association between an oncogene and an anti-oncogene: the adenovirus E1A proteins bind to the retinoblastoma gene product

Abstract: One of the cellular targets implicated in the process of transformation by the adenovirus E1A proteins is a 105K cellular protein. Previously, this protein had been shown to form stable protein/protein complexes with the E1A polypeptides but its identity was unknown. Here, we demonstrate that it is the product of the retinoblastoma gene. The interaction between E1A and the retinoblastoma gene product is the first demonstration of a physical link between an oncogene and an anti-oncogene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
702
1
10

Year Published

1990
1990
2006
2006

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,346 publications
(724 citation statements)
references
References 54 publications
10
702
1
10
Order By: Relevance
“…Indeed, major bands representing these proteins were named after their apparent SDS-PAGE molecular mass (Harlow et al, 1986), that is, p60, p105, p107, p130 and p300. The subsequent characterization of these proteins first identified p105 as the product of the RB gene (Whyte et al, 1988), and then p60 as cyclin A (Giordano et al, 1989;Pines and Hunter, 1990). Later, genes encoding p107 (Ewen et al, 1991;Zhu et al, 1993) and pRb2/p130 (Hannon et al, 1993;Li et al, 1993;Mayol et al, 1993) were cloned using different strategies.…”
Section: And References Therein)mentioning
confidence: 99%
“…Indeed, major bands representing these proteins were named after their apparent SDS-PAGE molecular mass (Harlow et al, 1986), that is, p60, p105, p107, p130 and p300. The subsequent characterization of these proteins first identified p105 as the product of the RB gene (Whyte et al, 1988), and then p60 as cyclin A (Giordano et al, 1989;Pines and Hunter, 1990). Later, genes encoding p107 (Ewen et al, 1991;Zhu et al, 1993) and pRb2/p130 (Hannon et al, 1993;Li et al, 1993;Mayol et al, 1993) were cloned using different strategies.…”
Section: And References Therein)mentioning
confidence: 99%
“…As interaction of Rb with other proteins has been demonstrated in a number of contexts (Chellappan et al, 1991;Dowdy et al, 1993;Gu et al, 1993;Hagemeier et al, 1993;Whyte et al, 1988), we hypothesized that a speci®c interaction might occur in F5-5 cultures upon activin treatment. F5-5 cells were cultured with or without activin and immunoprecipitated with rabbit anti-Rb antibodies or rabbit anti-CDK4 antibodies as control.…”
Section: Ectopic Expression Of Goosecoid (Gsc) In the Erythroblast Cementioning
confidence: 99%
“…These three proteins, pRB, p107 and p130, were ®rst described as targets of the adenovirus E1A oncoprotein which forms a complex with each of the RB-related proteins resulting in disruption of their normal function and deregulation of cellular growth control (reviewed in Whyte, 1995). Oncoproteins from other DNA tumor viruses including the SV40 large T antigen and HPV E7 proteins have been shown to target the RB-related proteins in a manner analogous to E1A (DeCaprio et al, 1988;Whyte et al, 1988;Dyson et al, 1989aDyson et al, , 1990Ludlow et al, 1990;Imai et al, 1991;Davies et al, 1993;Wolf et al, 1995). These observations ®rst suggested that the RB-related proteins (pRB, p107 and p130) control key checkpoints in cellular growth control.…”
Section: Introductionmentioning
confidence: 99%